Transmission route of SARS-CoV-2 and personal health intervention: a review on research advances - Hong-wei TU; Ping GAN; Ruo-xi ZHONG (Editorial Office of Chinese Journal of Public Health, 2022)
The conronavirus disease 2019 (COVID-19) pandemic exerts a major impact on the world. Understanding the transmission of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can help public health personnel to define the prevention and control priorities in practical work. This study summarized the existing literature (update to May 2, 2022) and analyzed and classified the main transmission routes of SARS-CoV-2 based on typical cases and laboratory studies, and proposed relevant prevention and personal protection strategies to provide a basis for more accurate and effective control of SARS-CoV-2 transmission.